Intravenous Immunoglobulin Combined With Corticosteroids for the Treatment of Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis: A Propensity-Matched Retrospective Study in China - Yang, Lu; Shou, Yan-Hong; Li, Feng; Zhu, Xiao-Hua; Yang, Yong-Sheng; Xu, Jin-Hua (Frontiers in Pharmacology, 2022)
Background: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare but life-threatening severe adverse drug reactions. The use of corticosteroids and intravenous immunoglobulin (IVIg) in SJS/TEN remains controversial. Methods: In this single-center, observational, propensity-matched, retrospective study, we collected a total of 224 patients with SJS/TEN who were hospitalized in our department from 2008 to 2019; according to treatment with IVIg combined with corticosteroids or with corticosteroids alone, patients were divided into combination therapeutic group (163 patients) and monotherapeutic group (61 patients). Patients from the two groups were matched by their propensity score in blocks of 2:1. Comparisons of the clinical characteristics and prognoses between propensity-matched SJS/TEN patients treated with IVIg combined with corticosteroids and corticosteroids alone were made. Results: After our propensity matching, a total of 145 patients were yielded, including 93 patients treated with IVIg and 52 patients not treated with IVIg. All of the 23 variables reflected good matching between patients treated with/without IVIg, and no significant difference was observed. Although there was no significant difference between the totally predicted and actual mortality in both of our groups, the actual mortality was lower than it was predicted in patients treated with IVIg [p > 0.250, the standardized mortality ratio (SMR) was 0.38, 95% CI 0.00–0.91] and patients treated without IVIg (p = 1.000, the SMR was 0.75, 95% CI 0.00–1.76). IVIg tended toward reducing the time to arrest of progression by 1.56 days (p = 0.000) and the length of hospital stay by 3.37 days (p = 0.000). The mortality rate was 45% lower for patients treated with IVIg combined with corticosteroids than those only treated with corticosteroid therapy, although it was not statistically significant (p = 0.555). The incidence of skin infections was significantly lower in the combined therapy group (p < 0.025), and the total infection rate of patients treated with combination therapy tended to decrease by 67% compared to patients treated with corticosteroids alone (p = 0.047). Conclusion: The actual mortality rate of patients treated with corticosteroids alone or IVIg combined with corticosteroids tended to be lower than those predicted by TEN-specific severity-of-illness score (SCORTEN), although there was no significance. Compared with those treated by corticosteroids alone, combination therapy was prone to bring a better prognosis for SJS/TEN patients.